2013
DOI: 10.1159/000351172
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-CVAD Regimen in Routine Management of Adult Acute Lymphoblastic Leukemia: A Retrospective Multicenter Study

Abstract: Treatment of acute lymphoblastic leukemia is unsatisfactory in adults due to disease and patient-related factors and probably because adult chemotherapy regimens are weaker than pediatric protocols. Worries about inadequacy of adult regimens urged many hematologists, including us, to reconsider their routine treatment practices. In this retrospective multicenter study, we aimed to evaluate results of hyper-CVAD treatment in comparison to other intensive protocols. All patients aged ≤65 years who were commenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
4
20
0
2
Order By: Relevance
“…However, we performed subgroup analysis and found that patients treated after 2006 had an NRM rate of~10%, which is acceptable according to the literature. 24 Importantly, haplo-HSCT was still superior to chemotherapy after 2006. Of course, future prospective studies are needed to confirm the benefits of haplo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, we performed subgroup analysis and found that patients treated after 2006 had an NRM rate of~10%, which is acceptable according to the literature. 24 Importantly, haplo-HSCT was still superior to chemotherapy after 2006. Of course, future prospective studies are needed to confirm the benefits of haplo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Buyukasik et al en Turquía, lo compararon con su régimen estándar (CALGB-8811) y, a pesar de que la tasa de remisiones completas fueron aceptables (84,2%), la mortalidad no asociada a recaída fue mayor (29,7% frente a 5,9%) (13) . Lu et al en China, compararon también su esquema estándar de dosis altas de AraC plus mitoxantrona frente a Hyper-CVAD y semejante a este reporte, a pesar de que no existieron diferencias significativas, la tasa de remisiones completas fue menor en el grupo de Hyper-CVAD (76% frente a 87%) (14) .…”
Section: Discussionunclassified
“…Aquellos pacientes no candidatos al régimen Hyper-CVAD fueron atendidos en base del protocolo Institucional HGMLAL07. Para demostrar la superioridad del régimen Hyper-CVAD sobre la tasa de remisiones completas, se calculó el número de pacientes necesarios a tratar en base a un poder del 80%, con una expectativa de éxito del régimen Hyper-CVAD del 89% (grupo 1) frente al resultado de remisiones completas ya conocido del régimen HGMLAL07 (68%) (13) . Se realizaron análisis secuenciales cada 4 meses y, en caso de que los resultados (remisiones completas) fueran inferiores que el régimen institucional, se daría por finalizado el enrolamiento y se suspendería el estudio y los pacientes subsecuentes serán atendidos con el protocolo institucional HGMLAL07.…”
Section: El Estudiounclassified
“…As a result, this rare cancer has no real ‘standard-of-care' in adults [2]. In this issue of Acta Haematologica, Buyukasik et al [3] report a retrospective comparison of 2 treatment approaches in adults.…”
mentioning
confidence: 99%
“…In this issue of Acta Haematologica, Buyukasik et al [3] report a retrospective analysis of newly diagnosed ALL patients treated at the same 4 institutions in Turkey either with hyper-CVAD (as originally reported in 2000) [5] or one of the commonly used BFM-based regimens [Cancer and Leukemia Group B (CALGB) 8811, reported in 1995] [6]. The overall results highlight the unsatisfactory outcome of adult ALL even among relatively young patients (65 years old or less, median age 30 years).…”
mentioning
confidence: 99%